2008
DOI: 10.1590/s0101-31222008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica e resistência do recobrimento de sementes de milho

Abstract: Este trabalho foi desenvolvido com o objetivo de avaliar a qualidade fisiológica de sementes de milho UENF 506-8 recobertas e a resistência do recobrimento utilizando diferentes proporções de cimentante. Foi utilizada no recobrimento das sementes uma mistura de calcário e meio de cultura. Como cimentante foi utilizada cola a base de acetato de polivinila (PVA). O recobrimento das sementes de milho foi realizado com uma mistura de 70% (p/p) de calcário, 10% (p/p) de meio de cultura semi-sólido JNFb e 20% (p/p) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
2
10
0
3
Order By: Relevance
“…The assessments were performed at 4 and 10 days after the start of the test (first count (FCG) and final germination (G), respectively), computing the number of normal seedlings, abnormal seedlings (AS) and non-germinated seeds (NGS), according to the criteria established by Brasil (2009), and the results expressed as a percentage. Throughout the test, daily counts were performed to determine the germination speed index (GSI) by the formula proposed by Maguire (1962) and the mean germination time (MGT), according to Edmond and Drapala (1958).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The assessments were performed at 4 and 10 days after the start of the test (first count (FCG) and final germination (G), respectively), computing the number of normal seedlings, abnormal seedlings (AS) and non-germinated seeds (NGS), according to the criteria established by Brasil (2009), and the results expressed as a percentage. Throughout the test, daily counts were performed to determine the germination speed index (GSI) by the formula proposed by Maguire (1962) and the mean germination time (MGT), according to Edmond and Drapala (1958).…”
Section: Methodsmentioning
confidence: 99%
“…Daily counts of the number of emerged plants were held for a period of 30 days. At the end, were determined the percentage of emergence (E), the emergence speed index (ESI), according to a formula by Maguire (1962), and the mean emergence time (MET), according to an adaptation by Edmond and Drapala (1958). At the end of 30 days, the plants were carefully removed from the trays and had their roots properly washed for measuring shoot length (SL) and root length (RL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results have showed that, for corn and lettuce crop, variations in coating composition and thickness alter emergence speed index, and it is associated to the development of a physical barrier on the outside of seed making the direct absorption of water and oxygen difficult (CONCEIÇÃO & VIEIRA, 2008). That pre-treatment of seeds through scarification and film coating may restrict moistening seeds of B. brizantha cv.…”
Section: (Usberti and Martins 2007)mentioning
confidence: 99%